A distinctive cytomorphological feature of interstitial pneumonia–related lung adenocarcinoma: The potential issues and solutions in practical diagnosis. Issue 3 (12th December 2022) - Sugiyama, Misaki; Matsumura, Mai; Sekiya, Motoki; Honda, Emi; Sekine, Akimasa; Arai, Hiromasa; Okudela, Koji
Abstract: Background: The cytological features of interstitial pneumonia (IP)–related lung adenocarcinoma (LADC) have not been clearly described. This study aimed to describe its cytomorphological features, uncover potential problems in practical cytological diagnosis, and provide possible solutions. Methods: Bronchial brushing cytology samples from 40 IP‐related LADC cases (the IP group) and 110 control cases (LADC unrelated to IP; the non‐IP group) were analyzed. All patients underwent surgery after brushing cytology, and their histopathological subtypes were determined. The authors reviewed the cytological features and focused particularly on cytoplasmic mucin production. Results: In the IP group, neoplastic cells with cytoplasmic mucin were detected at a significantly higher frequency (44.4% [8 of 18] vs. 6.3% [4 of 64]), and most of them were invasive mucinous adenocarcinomas (IMAs). Twenty‐two of the 40 LADC cases in the IP group failed to be judged as "malignant/positive" (thus, they were judged to be "equivocal and/or negative"). The frequency of equivocal and/or negative judgments was 55.0% (22 of 40) in the IP group and 41.8% (46 of 110) in the non‐IP group. The cytological diagnosis of IMA was difficult because it showed only slight nuclear atypia. Therefore, the authors examined the immunocytochemical expression of hepatocyte nuclear factor 4α (HNF4α), a diagnostic marker for IMA. As a result, four of the six cases that were judged to be equivocal in the IP group showed positive signals and could be retrospectively judged as malignant/positive. Conclusions: The cytological diagnosis of IP‐related LADC may be more difficult because of the larger proportion of IMA. Immunocytochemistry for HNF4α can be used to improve diagnostic confidence in IP‐related LADC. Abstract : The cytological diagnosis of interstitial pneumonia (IP)–related lung adenocarcinoma (LADC) may be more difficult because of the larger proportion of invasive mucinous adenocarcinoma. Immunocytochemistry for hepatocyte nuclear factor 4α can be used to improve diagnostic confidence in IP‐related LADC.